Treatment of Ventral Hernia Laparoscopic or Open Approach? - Espinosa, Miguel Fernando Maldonado; Erazo, Esteban Wilfredo Vivas; Villada, Nataly Zuluaga; Sánchez, David Alejandro Guzmán; García, Juan Sebastián Rivas; Peña, Carlos Alfredo Estrada; Mejía, Antonio Ortega; Rey, Javier Vargas; Pertuz, Jose Gregorio Villa (Jour Med Resh and Health Sci, 2022)
There are many different techniques currently in use for ventral hernia repair. Laparoscopic techniques have become more frequent in recent years, however, it is a subject associated with intense debate despite the fact that it has been shown to be a safe procedure with multiple benefits over the open approach; the latter constitutes a frequent complication after laparotomy with a reported incidence of up to 30%. Despite advances in surgical technique and prosthetic materials used, it represents a higher rate of recurrence and morbidity of up to 25%, mainly associated with seroma formation and surgical site infection. Despite the remarkable success of minimally invasive surgery, its use remains controversial.